PUSAT REHABILITASI ODHA DI BANJARMASIN - Adithia, Muhammad Farras; Febrita, Yuswinda; Wastuty, Prima Widya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Banjarmasin has the highest number of HIV/AIDS sufferers in South Kalimantan because the spread of HIV/AIDS is increasing significantly every day. The design of the HIV/AIDS Rehabilitation Center located on Jalan Pangeran Hidayatullah, East Banjarmasin, uses the concept of Healing Architecture, thus creating a rehabilitation building design which is expected to function as a means of physical and psychological rehabilitation with the hope that people infected with HIV will be free from depression and stress so that they can live like other normal humans, even though they have to take medication throughout their lives.